2012
DOI: 10.1177/0091270010395939
|View full text |Cite
|
Sign up to set email alerts
|

Limited Sampling Strategies for the Estimation of Raltegravir Daily Exposure in HIV‐Infected Patients

Abstract: Stepwise multiple regression analyses were applied to 50 raltegravir pharmacokinetic profiles from 50 HIV patients with the goal to identify limited sampling strategies for the prediction of drug area under the time-concentration curve (AUC(0-12)). Raltegravir single sampling point-based equations failed to reliably predict daily drug exposure. Conversely, different algorithms based on few samples and associated with good correlation, acceptable bias, and imprecision with the measured raltegravir AUC(0-12) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…It is more difficult to confirm this trend for novel drugs -namely darunavir, etravirine and maraviroc -simply because no clinical evidence is available to date correlating their plasma concentrations with toxicity. raltegravir exposure [23]. As confirmed by this and our previous findings, trough concentrations of raltegravir were associated with a very wide interpatient variability [22].…”
supporting
confidence: 87%
“…It is more difficult to confirm this trend for novel drugs -namely darunavir, etravirine and maraviroc -simply because no clinical evidence is available to date correlating their plasma concentrations with toxicity. raltegravir exposure [23]. As confirmed by this and our previous findings, trough concentrations of raltegravir were associated with a very wide interpatient variability [22].…”
supporting
confidence: 87%
“…Indeed, phase II/III trials have shown that RAL plasma concentrations and drug exposure were correlated with the efficacy outcome, whereas no relevant clinical associations were found with the RAL C trough (11,13,16). The latter finding was not unexpected, given the failure of the RAL C trough to reliably predict daily drug exposure, expressed as RAL AUC 0-12 (5). In the present study, we have shown that patients taking RAL by swallowing whole tablets experienced a wide distribution in the main drug pharmacokinetic parameters.…”
Section: Discussionsupporting
confidence: 64%
“…For most antiretrovirals, TDM is usually performed by assessing the single plasma trough concentration (C trough ). However, this approach is not feasible for RAL, which requires routine assessment of the predicted area under the concentration-time curve (AUC) (5). The assessment of RAL plasma concentrations was therefore carried out as routine TDM based on the collection of blood samples within the first 4 h after the morning RAL dose.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations